2020
DOI: 10.1002/eji.202070125
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 lock‐downs for European (female) immunologists – our views as members of the EFIS gender and diversity task force

Abstract: The impact of COVID-19 lock-downs for European (female) immunologists-our views as members of the EFIS gender and diversity task force EFIS action towards gender and diversity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…This increased burden of women’s care work also blocked their performance and representation in paid productive work as they needed to balance paid work and domestic work. This reiterates Esser et al ( 2020 ) research from ten countries across Europe that reported similarities in the discriminatory burden of care-work on women. For instance, they assert that in Spain, challenges of increased tasks for carers (mothers of young children or those with sick dependents in the household) affected their productive work (Esser et al, 2020 ).…”
Section: Covid-19 and Its Effects On Women’s Unpaid Worksupporting
confidence: 79%
“…This increased burden of women’s care work also blocked their performance and representation in paid productive work as they needed to balance paid work and domestic work. This reiterates Esser et al ( 2020 ) research from ten countries across Europe that reported similarities in the discriminatory burden of care-work on women. For instance, they assert that in Spain, challenges of increased tasks for carers (mothers of young children or those with sick dependents in the household) affected their productive work (Esser et al, 2020 ).…”
Section: Covid-19 and Its Effects On Women’s Unpaid Worksupporting
confidence: 79%
“…While the year 2020 is behind us, the ongoing pandemic continues to pose challenges for our global research community, especially those of us with small children. COVID-19 pandemics and lockdowns have negatively impacted primarily female scientists [4] and we could clearly witness this while preparing the 50 th Anniversary Collection. Although a number of female authors and key opinion leaders contributed to the current series, several lead female immunologists, despite initial enthusiasm to contribute, were finally not able to, since their regular daily roles as lab heads have suddenly switched to full time child-care and home schooling.…”
Section: Editorialmentioning
confidence: 99%
“…Traditionally held at ECIs since 2015, the “ Women and Men in Immunology ” session [1] to discuss gender inequality issues in the immunology field and in academia will be organized by the newly formed EFIS Diversity Task Force this year. This special session will focus on the impact of the COVID‐19 pandemic on women immunologists, an issue which has already been highlighted by the Taskforce [2]. The Organizers will also present the “Professor Isil Berat Barlan Awards” and the “EFIS Diversity Task Force Publication Award” at the end of this session.…”
mentioning
confidence: 99%